Trade costs, time, and supply chain reliability. - Utsav,Kumar (Metro Manila, Philippines Asian Development Bank, 2018)
This paper uses measures of international transport time in median and standard deviation based on shipment level data from the Universal Postal Union, to analyze the effect of time on trade costs. The results show that median shipping times increase trade costs by a substantial amount. The determinants of shipping times are also analyzed and find that geographical distance is the most reliable indicator of median time and uncertainty, with logistics performance also playing a role in determining shipment times.
Keywords: Trade regulation; Trade regulation -- Case studies; Trade regulation -- International cooperation; Electronic books